2012
DOI: 10.1158/1055-9965.epi-11-1205
|View full text |Cite
|
Sign up to set email alerts
|

Aromatic DNA Adducts and Risk of Gastrointestinal Cancers: A Case–Cohort Study within the EPIC–Spain

Abstract: Background: Colorectal (CRC) and gastric cancer (GC) are associated with meat intake and tobacco smoke, maybe because of aromatic compounds occurring in tobacco smoking and formed during cooking meat. Activated metabolites of these compounds may bind to DNA forming bulky adducts.Methods: Forty-eight subjects diagnosed of GC and 154 of CRC during a 7-year follow-up period in the European Prospective Investigation into Cancer and Nutrition-Spain cohort were compared with a sample of 296 subjects using a case-coh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 30 publications
0
19
0
2
Order By: Relevance
“…However, this study was limited by a relatively small number of cases of colorectal adenoma (N=82), and blood samples were collected after diagnosis. More recently, Agudo et al [12] conducted a case-cohort study evaluating the relationship between aromatic DNA adduct levels in pre-diagnostic leukocytes and risk of colorectal cancer (154 cases). The investigators reported a statistically significant increased risk of colorectal cancer with increasing levels of aromatic DNA adducts, and observed a stronger association for colon cancer than for rectal cancer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, this study was limited by a relatively small number of cases of colorectal adenoma (N=82), and blood samples were collected after diagnosis. More recently, Agudo et al [12] conducted a case-cohort study evaluating the relationship between aromatic DNA adduct levels in pre-diagnostic leukocytes and risk of colorectal cancer (154 cases). The investigators reported a statistically significant increased risk of colorectal cancer with increasing levels of aromatic DNA adducts, and observed a stronger association for colon cancer than for rectal cancer.…”
Section: Discussionmentioning
confidence: 99%
“…However, few studies have evaluated the relationship between PAH exposure biomarkers and risk of colorectal adenoma [11] or colorectal cancer [12]. In this nested case–control study, we evaluated the risk of colorectal cancer in relation to urinary concentration of 1-hydroxypyrene glucuronide (1-OHPG), a metabolite of pyrene and an established biomarker of PAH exposure [13], among participants in the Shanghai Women’s Health Study.…”
Section: Introductionmentioning
confidence: 99%
“…However, 32 P‐postlabeling is labor‐intensive and requires large amounts of hazardous radioactivity, the technique is not quantitative, and structural information about the identity of the adduct is uncertain, particularly in humans where many overlapping lesions are present . Thus, epidemiology studies employing 32 P‐postlabeling often provide ambiguous data about chemical exposures linked to DNA adducts and cancer risk …”
Section: Methods To Biomonitor Dna Adducts In Humansmentioning
confidence: 99%
“…Many DNA adducts serve as biomarkers of carcinogenic PAH exposure and cancer risk (Phillips and Venitt 2012; Poirier 1997; Urban et al 2012). Significant positive linear correlations between levels of PAH-DNA adducts and cancer incidence have been reported in both epidemiological studies (Agudo et al 2012; Tang et al 2001; Veglia et al 2008) and animal experiments (Culp et al 1998). However, negative correlations between PAH-DNA adducts and tumor incidence have also been observed (Saieva et al 2011; Siddens et al 2012) and the mechanic relationships between carcinogen-DNA adducts and tumor formation are still not fully understood.…”
Section: Introductionmentioning
confidence: 96%